Epoxidized jatropha oil as a sustainable plasticizer to poly(lactic acid) - Chieng, Buong Woei; Ibrahim, Nor Azowa; Then, Yoon Yee; Loo, Yuet Ying (MDPI, 2017)
A renewable resource, epoxidized jatropha oil (EJO), was used as a green plasticizer and added to poly(lactic acid) (PLA). EJO was compounded into PLA at different contents. The addition of 3 wt % EJO to the PLA demonstrates significant improvement in flexibility, which leads to a percentage increase of about 7000% in elongation at break. This tensile result was confirmed by surface morphology analysis with clear proof of plastic deformation in EJO-plasticized PLA. EJO imparts a good heat stabilization effect. Thermal stability of PLA was enhanced upon addition of EJO, which is due to their good interaction and plasticizer dispersion within the PLA matrix. This EJO-plasticized PLA has wide applications in various industries, such as packaging of food and non-food products.